A STUDY ON AWARENESS AND PREFERENCE OF WOMEN IN FINANCIAL ASSETS FOR INVESTMENT IN GUWAHATI CITY, ASSAM - Mazumder, Deepika; Das, Sweety (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The evolving financial landscape in India has brought about significant changes in the role of women in financial decision-making, from traditional domestic roles to active, independent financial choices. This study examines the awareness, preferences, and underlying influences guiding women’s investment behavior in Guwahati, Assam. Given the increasing independence and financial literacy among women, it is crucial to understand their awareness and preferences for various financial assets, the factors affecting these choices. Using a descriptive research design, primary data was collected from 100 women through a structured questionnaire with simple random sampling. Findings suggest that while women exhibit familiarity with low-risk assets like bank deposits and mutual funds, knowledge gaps and risk aversion limit engagement with riskier assets like equities. Recommendations are provided for targeted financial literacy programs, focusing on enhancing understanding and engagement with diverse investment options to support individual financial empowerment and contribute to national economic growth.